Standardization Of Meat Randang Recipes At Maninjau Village Agam District - Nauman, Aldip; Syarif, Wirnelis (Universitas Negeri Padang, 2022)
This research was conducted to produce literature. There is no standard recipe for beef randang recipe, and there is no documented recipe in the form of book. This study aims to produce a standard recipe and quality of beef randang in the maninjau village in Agam distict starting from May to June 2021. There are two sources of data; qualitative data sources, which are taken from 5 informants who are experts in making beef randang in Maninjau Village in Agam District, and quantitative data collection technique is using organoleptic test questionnaire format and using the formula (MX=ΣX/N). Based on the results of the study, it was obtained that the beef randang recipe includes the ingredients used, the number of ingredients, how to make it, and the quality of the beef randang so that produce a converted recipe. Furthermore, organoleptic tests were carried out on the quality to get a good quality of beef randang, including: the shape of randang, the meat is quite square, blackish brown, smells good, the meat is soft textured, and the meat is savory.